Human Ia-like antigens in non-lymphoid organs. - Koyama, K (1979)
Human Ia-like antigens in liver and kidney were shown by the immunofluorescence assay to be present mostly in the endothelial-mesenchymal cells of these organs. The parenchymal cells apparently contained no human Ia-like antigens. The antigens in liver and kidney were purified and shown to have the same subunit structure as human Ia-like antigens of cultured B-lymphoid cells. The human Ia-like antigens in non-lymphoid organs, not only in liver and kidney but also in testis, heart, muscle and brain, carried all the xenoantigenic characteristics of human Ia-like antigens expressed on lymphoid cells of B-cell lineage.